2015
DOI: 10.1190/geo2014-0572.1
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic rupture propagation imaging

Abstract: We have developed a method for tracing the rupture propagation of microseismic events. We referred to it as microseismic rupture propagation imaging (MRPI), which is an adaptation of the back projection technique from global seismology. Hence, we shifted back recorded waveforms to a grid of possible source locations and obtained a coherent phase stack that migrated according to the migration of the rupture front. Using synthetic ruptures and the corresponding waveforms obtained by finite-difference modeling, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The relative diversity of rupture directions close to the injection source and the increasing alignment of rupture directions with larger distances coincide with the decreasing effect of the pore pressure with larger distances, which also seems to control the observed stress drop [Goertz-Allmann et al, 2011] and role of Coulomb stress changes [Catalli et al, 2013] at Basel. The distinct behavior of the largest events, which rupture preferentially backward to the injection source agrees with independent observations from direct rupture imaging of M L ≥ 3.2 events at Basel [Folesky et al, 2015]. These events also occur close to the boundary of the stimulated volume.…”
Section: Discussionsupporting
confidence: 87%
“…The relative diversity of rupture directions close to the injection source and the increasing alignment of rupture directions with larger distances coincide with the decreasing effect of the pore pressure with larger distances, which also seems to control the observed stress drop [Goertz-Allmann et al, 2011] and role of Coulomb stress changes [Catalli et al, 2013] at Basel. The distinct behavior of the largest events, which rupture preferentially backward to the injection source agrees with independent observations from direct rupture imaging of M L ≥ 3.2 events at Basel [Folesky et al, 2015]. These events also occur close to the boundary of the stimulated volume.…”
Section: Discussionsupporting
confidence: 87%
“…Although the Basel geothermal project failed, the collected data of the induced seismicity improved our understanding of EGS in several scientific studies that investigated the reservoir structure and the orientation of fault planes (e. g., Asanuma et al, ; Dyer et al, ; Dyer et al, ; Deichmann et al, ; Kraft & Deichmann, ), performed statistical analyses for earthquake forecasting purposes (e.g., Bachmann et al, ; Mena et al, ; Gischig & Wiemer, ; Király‐Proag et al, ), modeled geomechanical properties (e.g., Goertz‐Allmann et al, ; Goertz‐Allmann & Wiemer, ; Bachmann et al, ), studied the larger events in terms of their trigger mechanism (e.g., Mukuhira et al, ) and rupture propagation (e.g., Folesky et al, ), analyzed ground motion and macroseismic intensities (e.g., Edwards et al, ; Ripperger et al, ), and performed seismic risk analysis (e.g., Baisch et al, ; Mignan et al, ). These studies benefited from the six‐station borehole seismometer network (three stations used in this study are shown in Figure ) and a surface network with 30 stations in the area (Deichmann & Ernst, ).…”
Section: Introductionmentioning
confidence: 99%
“…Older studies usually dealt with rupture properties of single earthquakes (Jost et al, 1998;Li et al, 1995), and only recently, larger sets of events were examined for complexities or directivity (Abercrombie et al, 2017;Calderoni et al, 2015;Kane et al, 2013;Lengliné & Got, 2011;Ross & Ben-Zion, 2016). Recent studies also analyzed microseismic events (Dreger et al, 2007;Folesky et al, 2015Folesky et al, , 2016Taira et al, 2015) in an effort to connect with the scales from physical rupture modeling in the laboratory and numerical modeling (e.g., Kaneko & Shearer, 2014Lapusta et al, 2000).…”
Section: Introductionmentioning
confidence: 99%